P22 Using an elastomeric pump to administer continuous infusions of antibiotics as part of an outpatient parenteral antimicrobial therapy (opat) programme. Issue 2 (19th January 2018) - Sharpe, David; Crouch, Claire; Porter, David; Paulus, Stephane
Abstract : Aims: Continuous intravenous infusion using an elastomeric pump is an alternative delivery method in paediatric patients who need intravenous antibiotics (IVAB) which would otherwise need to be administered three times daily, such as piperacillin/tazobactam or ceftazidime. 1 We describe our experience using elastomeric pumps in the OPAT setting. Methods: A retrospective case series of 5 children (aged 5–17 years) discharged home on IVAB continuous infusion administered via an elastomeric pump. One child received this mode of delivery twice therefore 6 patient-episodes are described in this case series. Outcomes were assessed using the BSAC p-OPAT (British Society of Antimicrobial Chemotherapy Paediatric-OPAT) criteria. Ethics approval was not required because the information was gathered retrospectively and patient data has been anonymised. Results: In 5 of the episodes the indication was lower respiratory tract infection treated with continuous IV piperacillin/tazobactam. All patients had a background of neurodisability, recurrent respiratory tract infections and Pseudomonas aeruginosa carriage. The remaining patient was treated for an infective exacerbation of cystic fibrosis with a regimen that included continuous IV ceftazidime. All episodes had an outcome defined as 'Success' according to the BSAC p-OPAT criteria; having an infection outcome of 'improved' or 'cured' with no adverse events reported. Conclusions: The successful outcomes in this case series suggest that elastomeric pumps are a safe and effective option for administering selected antibiotics by continuous IV infusion to children, although central venous access is a requirement. This option should be considered to facilitate the early discharge of patients to be treated with IVAB such as piperacillin/tazobactam under the guidance of an OPAT service. Reference: Patel S, Abrahamson E, Goldring S, Green H, Wickens H, Laundy M. Good practice recommendations for paediatric outpatient parenteral antibiotic therapy (p-OPAT) in the UK: A consensus statement. J Antimicrob Chemother2015;70(2):360–73.